Challenges for a shared European countryside of uncertain future. Towards a modern community-based landscape perspective. - Pedroli, B. (2016)
This paper addresses current changes in the highly diverse European landscape, and the way these transitions are being treated in policy and landscape management in the fragmented, heterogeneous and dynamic context of today’s Europe. It appears that intersecting driving forces are increasing the complexity of European landscapes and causing polarising developments in agricultural land use, biodiversity conservation and cultural landscape management. On the one hand, multifunctional rural landscapes, especially in peri-urban regions, provide services and functions that serve the citizens in their demand for identity, support their sense of belonging and offer opportunities for recreation and involvement in practical landscape management. On the other hand industrial agricultural production on increasingly large farms produce food, feed, fibre and energy to serve expanding international markets with rural liveability and accessibility as a minor issue. The intermediate areas of traditionally dominant small and family farms in Europe seem to be gradually declining in profitability. The paper discusses the potential of a governance approach that can cope with the requirement of optimising land sharing conditions and community-based landscape development, while adapting to global market conditions.